Pengaruh Kualitas Pelayanan dan Lokasi Usaha Terhadap Loyalitas Pelanggan di Toko Grosir Mutmainah Kudus dengan Kepuasan Konsumen Sebagai Variabel Mediasi - Manunal Ahna Zanuba; Muhammad Faisal Yul Zamrudi (As-Syirkah: Islamic Economic & Financial Journal, 2026)
Competition in today’s business world is increasingly fierce. This is also felt by business owners in the trading sector, such as the owner of the Mutmainah Kudus Wholesale Store. The Mutmainah Kudus Wholesale Store is one of the largest wholesale stores in Kudus City. The Mutmainah Kudus Wholesale Store must understand the factors that influence customers satisfaction. The Mutmainah Kudus Wholesale Store must make several improvements and innovations to increase customer satisfaction. This study aims to analyze the influence of service quality and business location on customer loyalty, with customer satisfaction as the mediating variable. This study is a qualitative study, which is descriptive and tends to use analysis. The population in this study was all customers of the Mutmainah Kudus Wholesale Store. The sample in this study was thirty customers of the Mutmainah Kudus Wholesale Store aged seventeen years and above. The results of this study indicate that the variabels of service quality and business location studied have a positive effect on customer satisfaction. Furthermore, the customer satisfaction variable also showed a significant positive effect on customer loyalty.